PENGARUH CARBON CREDIT, FIRM SIZE, DAN GOOD CORPORATE GOVERNANCE TERHADAP KINERJA PERUSAHAAN PADA PERUSAHAAN MANUFAKTUR YANG TERDAFTAR DI BURSA EFEK INDONESIA - Ni Made Dwi Ratna Sari; I Gusti Ayu Agung Omika Dewi (Jurnal Ilmiah Akuntansi & Bisnis, 2019)
The Influence of Carbon Credit, Firm Size, and Good Corporate Governance on Performance of Public Listed Manufacturing Companies. This study aims to examine the effect of carbon credit, firm size, board of commissioners and audit committee on company performance. The population used in this study is manufacturing companies listed on the Indonesia Stock Exchange. The method of sample selection is purposive sampling. Only 25 companies meet the criteria. The hypotheses in this study were tested using t test and f test. The data analysis technique used in this study was multiple linear regression test. The results of the study indicate that carbon credit, firm size, board of commissioners and audit committee partially and simultaneously influence performance of public listed manufacturing companies.Keyword: Carbon credit, firm size, board of commisioners, audit committee